MODEL PEMBELAJARAN KETERAMPILAN BINA DIRI BAGI ANAK USIA DINI TUNAGRAHITA - Putri, Ni Luh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2014)
Abstract: This study aims to develop a learning model of Self-Care skills for mentally retarded early age children in North Sulawesi. The research was conducted in five exceptional schools in North Sulawesi which includes 10 teachers and 22 mentally retarded early age children. This study used a qualitative approach while methods of research include research and development (R&D) procedures. This Self-Building learning model were developed in four phases, which are (1) requirements analysis, (2) designing model based on the results of requirements analysis, (3) implementation of the learning model, and (4) assess the effectiveness of learning models in accordance with the teaching process. The evaluation process consist of expert matters validation, which are early age education and mentally retarded children experts, and making revision. Validation was implemented by the teachers of mentally retarded exceptional schools before making a revise, first field trials, second field trials and field tests. The trial results used to revise the product. This research resulted in RPP (Learning Implementation Plan) and a handbook for teachers. Conclusions from the study were: Implementation of the resulting learning model was effective to improve the mastery of skills to take off and put on shoes, socks, a shirt, t-shirt, short, skirt for the mentally retarded early age; The substance of the content and design flexibility of the structure of the model are included in the category of effective and the application of teaching learning model will be able to facilitate the teachers of mentally retarded exceptional School Learning Implementation Plan, carry outa learningand undertake an evaluation of learning. Abstrak: Penelitian ini bertujuan untuk mengembangkan model pembelajaran keterampilan bina diri untuk keterbelakangan mandiri pada anak usia dini di Sulawesi Utara. Penelitian ini dilaksanakan di sekolah luar biasa di Sulawesi Utara dengan melibatkan 10 orang guru dan 22 anak usia dini dengan keterbelakangan mental. Penelitian ini menggunakan pendekatan kualitatif dengan metode Research and Development (RnD). Model pembelajaran dilakukan dalam empat asa, yaitu (1) analisis kebutuhan, (2) mendisain model pembelajaran berdasarkan hasil analisis kebutuhan, (3) menerapkan model pembelajaran, dan (4) menilai keefektifan model pembelajaran sesuai dengan proses mengajar. Proses evaluasi berisi validasi meteri oleh ahli, oleh pendidik anak usia dini dan ahli keterbelakangan mental pada anak, dan membuat revisi. Validasi diterapkan oleh guru keterbelakangan mental di sekolah luar biasa sebelum membuat perbaikan, uji coba lapangan pertama, uji coba lapangan kedua, dan uji lapangan. Uji tersebut digunakan untuk memperbaik produk. Penelitian ini menghasilkan RPP (Rencana Pelaksanaan Pembelajaran) dan handbook untuk guru. Kesimpulannya dari penelitian ini adalah: penerapan menghasilkan model pembelajaran yang efektif untuk menghasilkan keterampilan dalam melepaskan dan memakai sepatu, kaus kaki, baju, kaus, dan senda untuk anak keterbelakangan mental. Substansi dari isi dan fleksibilitas desain dari struktur model termasuk didalamnnya kategori efektivitas dan penerapan model pembelajaran dan pengajaran akan mampu memfasilitasi guru di sekolah luar biasa dalam menerapkan pembelajaran, melaksanakan pembelajaran dan melakukan evaluasi pembelajaran.